Ionic conduction in Mg2+ and Sr2+ co-doped ceria/carbonates nanocomposite electrolytes. (2nd March 2015) - Jaiswal, Nandini; Upadhyay, Shail; Kumar, Devendra; Parkash, Om
Abstract Nanocomposite electrolytes consisting of Mg2+ and Sr2+ co-doped ceria (CM6S4) and eutectic mixture of (Li–Na)2CO3 (LNCO) have been synthesized and characterized using XRD and SEM. Thermal expansion and electrical conductivity have been studied as a function of temperature. All the samples have fluorite structure similar to ceria and carbonates are present as an amorphous phase surrounding the ceria phase. Impedance measurements have been made in air in the temperature range 200–650 °C. Conductivity of the composites increases very rapidly around the softening temperature of the carbonates. After melting, carbonates fill in the interspaces of the ceria phase and form a percolated network. This leads to the formation of high conducting pathways at the interfaces. Composition CM6S4/35LNCO shows the highest conductivity, 0.4 S/cm at 500 °C which is two orders of magnitude higher than that of CM6S4 (2.4 × 10−3 S/cm). This improvement in the conductivity has been ascribed to the interfacial ionic conduction.